Educational Perspectives on the #KaburAjaDulu Phenomenon and Youth Social Behavior in Indonesia - Syifa Nur Syiami; Irawati (Yayasan Cerdas Pedia Indonesia, 2025)
This research investigates the viral #KaburAjaDulu phenomenon in Indonesia as a critical response to socio-economic crises in 2025. Employing digital ethnography and systematic literature review, the study analyzes how legislative shocks, specifically Inpres No. 1/2025, and economic instability drive youth toward migration. Applying Stag Hunt game theory and Bourdieu’s cultural capital, it identifies a